2020
DOI: 10.1534/g3.120.401684
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the F Locus Responsible for Floral Anthocyanin Production in Potato

Abstract: Anthocyanins are pigmented secondary metabolites produced via the flavonoid biosynthetic pathway and play important roles in plant stress responses, pollinator attraction, and consumer preference. Using RNA-sequencing analysis of a cross between diploid potato (Solanum tuberosum L.) lines segregating for flower color, we identified a homolog of the ANTHOCYANIN 2 (AN2) gene family that encodes a MYB transcription factor, herein termed StFlAN2, as the regulator of anthocyanin production in potato corollas. Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Secondly, R2-R3 MYB transcription factors showing homology with Petunia AN2 gene (Borevitz2000) regulate anthocyanin biosynthesis in dicotyledonous plants [ 76 80 ]. A number of these AN2 homologs regulate the expression of anthocyanin enzymes in tubers and flowers of potato [ 33 , 35 , 37 ], including three nearby genes from chromosome 10 named StAN1 , StAN2 and StFlAN2 . The Myb12 TF detected in this study has not been linked to anthocyanin production in potatoes but it´s orthologs regulate anthocyanin production in other plants like Arabidopsis thaliana [ 81 ], apple [ 82 ], lily [ 83 , 84 ], and grape [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Secondly, R2-R3 MYB transcription factors showing homology with Petunia AN2 gene (Borevitz2000) regulate anthocyanin biosynthesis in dicotyledonous plants [ 76 80 ]. A number of these AN2 homologs regulate the expression of anthocyanin enzymes in tubers and flowers of potato [ 33 , 35 , 37 ], including three nearby genes from chromosome 10 named StAN1 , StAN2 and StFlAN2 . The Myb12 TF detected in this study has not been linked to anthocyanin production in potatoes but it´s orthologs regulate anthocyanin production in other plants like Arabidopsis thaliana [ 81 ], apple [ 82 ], lily [ 83 , 84 ], and grape [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Liu and colleagues [ 97 ] found that changes in the expression of this gene are involved in anthocyanin biosynthesis under heat stress. Additionally, the upregulation of this gene is associated with a greater accumulation of anthocyanins in potato flowers [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations